Fetal sexing in bovine embryos for in vitro production – literature review. - de Lucena, Larissa Marques; Delfino, Karina da Silva; Prazeres , Talyta Alves; da Silva, Weslley Garcia; Ferrer, Daniela Mello Vianna; Leite , Dala Kezen Vieira Hadman (Seven Editora, 2023)
The genetic improvement in animal production has been expanding day by day. Cattle farming is an area that increasingly needs the use of biotechnologies because commercially, the birth of genetically improved calves has been essential to ensure the quality of the herd. The early diagnosis of the fetus has helped producers to guide their strategies along the production chain, whether in dairy or beef cattle. Cattle farming is efficient regarding the use of biotechnologies for genetic improvement. The agricultural sector has been seeking to revolutionize animal production, for sustainable use, prioritizing animal welfare without harming profits. Factors such as nutrition, management, and health have been implemented in dairy farms to help these animals express their genetic potential (BECHER et al., 2018).DOI:https://doi.org/10.56238/alookdevelopv1-047